Strain engineering in epitaxial Ge1−xSnx: a path towards low-defect and high Sn-content layers. (20th November 2017) - Margetis, Joe; Yu, Shui-Qing; Bhargava, Nupur; Li, Baohua; Du, Wei; Tolle, John
Abstract: The plastic strain relaxation of CVD-grown Ge1− x Sn x layers was investigated in x = 0.09 samples with thicknesses of 152, 180, 257, 570, and 865 nm. X-ray diffraction-reciprocal space mapping was used to determine the strain, composition, and the nature of defects in each layer. Secondary ion mass spectrometry was used to examine the evolution of the compositional profile. These results indicate that growth beyond the critical thickness results in the spontaneous formation of a relaxed and highly defective 9% Sn layer followed by a low defect 12% Sn secondary layer. We find that this growth method can be used to engineer thick, strain-relaxed, and low defect density layers. Furthermore we utilize this strain-dependent Sn incorporation behavior to achieve Sn compositions of 17.5%. Photoluminesence of these layers produces light emission at 3.1 μ m.